PENEGAKAN HUKUM PIDANA TERHADAP CYBER CRIME DI INDONESIA - Hutajulu, Andreas Fransiskus; Wahyuningsih, Sri Endah (Ensiklopedia of Journal, 2025)
Abstract: Cybercrime regulations are scattered across both the Indonesian Criminal Code (KUHP) and outside of it. For instance, Law No. 36 of 1999 on Telecommunications was introduced to complement the KUHP. However, several issues arise in regulating cybercrime, as some forms of cybercrime can be sanctioned under existing Indonesian laws, while others remain beyond the current legal reach. For example, if a criminal act contains elements defined as a criminal offense under the KUHP but does not meet all legal requirements such as in hacking cases a legal vacuum (vacuum legis) occurs. Therefore, the KUHP and the Electronic Information and Transactions Law (UU ITE) must align in implementing norms for cyber offenses, including offenses in the field of information technology. This alignment represents a future criminalization policy (ius constituendum) in anticipation of the development of cybercrime.Keywords: Law Enforcement, Cyber Crime, Indonesia.